Intangible Cultural Heritage as an Opportunity for the Development of Armenian Studies - Tsaturyan, Ruzanna (History and Culture, 2025)
In recent decades, the field of intangible cultural heritage (ICH) has become one of the priorities of global cultural policy. Beyond focusing on tangible structures and sites, international cultural policy has begun to emphasize traditions and their bearers, considering them crucial for the future preservation of cultural heritage within modern cultural environments. In 2006, the Republic of Armenia ratified UNESCO's 2003 Convention for the Safeguarding of the Intangible Cultural Heritage, thus aligning itself with the international agenda.Incorporating elements of a country's cultural heritage into various international and national lists of intangible heritage involves more than bureaucratic and state policy processes; it primarily requires substantive and conceptual approaches. In this regard, Armenian studies play a decisive role. This paper explores the opportunities and potential of Armenian studies within the context of dynamic global and local ICH policy developments. Key issues discussed include re-evaluating methodological approaches in research in Armenian studies, the potential for "translating" Armenia’s cultural heritage and representing it in global databases, and the challenges and opportunities of creating a research environment that supports ICH standards.At the same time, the field of intangible cultural heritage offers methodological potential for Armenian studies, particularly in conducting interdisciplinary research with real policy impact. Realizing this potential could be mutually beneficial for both the advancement of Armenian studies and the preservation of intangible cultural heritage.